Pelatihan Komunikasi Lintas Bahasa untuk Masyarakat Desa Wisata di Desa Kadugenep - Ria Saraswati; Malabay, Malabay; Yuliati, Yuliati (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Kadugenep Tourism Village holds great potential as a culturally based tourist destination. However, language barriers remain a significant challenge for the local community in providing services to international visitors. This cross-language communication training aims to improve the villagers' foreign language skills, particularly in tourism contexts, to enhance service quality and the village's overall appeal. This study employs a qualitative method with a participatory training approach, incorporating observation, interviews, and skill evaluations before and after the training. Findings indicate a significant improvement in basic English communication skills and a deeper understanding of tourist cultures post-training. Additionally, villagers gained greater confidence in interacting with foreign visitors. The implications of this study suggest that cross-language communication training contributes to enhancing the competitiveness of Kadugenep Tourism Village and can serve as a model for other tourism villages. With continued support, such initiatives could foster sustainable tourism, empower local communities economically and socially, and strengthen intercultural exchange between hosts and visitors, making local destinations more accessible and attractive to a global audience.